An inventory of crop wild relatives and wild‐utilized plants in Canada. Issue 6 (12th October 2022) - Ulrich, Jens C.; Moreau, Tara L.; Luna‐Perez, Erika; Beckett, Kephra I. S.; Simon, Lili K.; Migicovsky, Zoë; Diederichsen, Axel; Khoury, Colin K.
Abstract: In the face of global pressures of change and biodiversity loss, crop wild relatives (CWR) and wild‐utilized species (WUS) urgently require conservation attention. To advance conservation, we assembled a national inventory of CWR and WUS in Canada. To assess current ex situ conservation of these plant species, we gathered a virtual metacollection of accession data from botanical gardens and national genebanks. The inventory includes 779 CWR and WUS taxa (658 distinct species), with 263 (222 distinct species) that are related to food crops of national and global importance such as blueberry ( Vaccinium corymbosum L.), apple ( Malus domestica (Suckow) Borkh.), sunflower ( Helianthus annuus L.), and saskatoon ( Amelanchier spp.). Sixty‐one food crop relatives are prioritized for breeding potential, and sixteen due to conservation threats. Although most food crop CWR are represented in ex situ collections (91% of species), representation of within‐species diversity is low (median = 5% of Canadian ecogeographic types represented per species). Poor representation of within‐species diversity demands an integrative conservation strategy that emphasizes in situ protection, especially focusing on wild populations in Canada's southern ecoregions where diversity is concentrated. While genebank collections represent higher accession counts per species, botanical gardens include living collections of fruit crop relatives and other woody perennials that are well situated to raise broader awareness of CWR and WUS. To promote further conservation action, we present a web application that enables conservation planners and practitioners to identify local CWR and WUS and to identify within‐species ecogeographic types that are underrepresented in ex situ conservation systems. Core Ideas: Canada contains a rich diversity of crop wild relatives and wild‐utilized species, including many relatives of fruit crops. The 61 Canadian food crop wild relatives have high potential utility in crop breeding, and 17 are nationally imperiled. Living collections of woody‐perennial crop wild relatives and wild‐utilized species in botanical gardens complement ex situ conservation in genebanks. Conservation requires integrative strategy, with coordinated in situ action prioritizing Canada's southern regions. Display collections in gardens and new, online tools are situated to advance conservation by raising engagement.